Differences in Prostaglandin f2α Level in Adolescent Girls Experienced and Not Experienced Premenstrual Syndrome: A Cross-Sectional Study - Ruqaiyah, Ruqaiyah; Wulandari, Ikrawanti Ayu; Harun, Ayatullah; Irwan, Hadriani; Amir, Fatmawati; Alamsyah, Alamsyah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This study aims to determine the differences in Prostaglandin f2α concentration in female adolescents who experienced and did not experience Pre-Menstrual Syndrome (PMS). Cross-sectional study conducted at a single institution. The sample for this study was female adolescents at the Darul Arqam Islamic Boarding School in Makassar, consisting of 50 adolescents who experienced PMS and those who did not experience PMS in a ratio of 1:1. Prostaglandin f2α levels were measured using an ELISA kit. The sample used was 5 cc blood from the median cubital vein by laboratory staff 5 days before menstruation. Data were analyzed descriptively and statistically. The results showed that the average Prostaglandin f2α in the group that experienced PMS (379.07) was higher compared to the group that did not experience PMS (101.23) with a p-value < 0.05, significantly. Furthermore, the group that experienced mild PMS had an average Prostaglandin f2α value of 283.32, while the group that experienced severe PMS had an average Prostaglandin f2α value of 454.31. The average Prostaglandin f2α level in the group who did not experience PMS, mild PMS, and severe PMS had a p-value < 0.05. This study concludes that there is a significant difference in the Prostaglandin f2α Level in adolescents who experience PMS and those who do not experience it and there are differences based on the severity of PMS.